Effects of biochar on phosphorus fraction, phosphatase activity, and phosphorus-solubilizing bacterial abundance: a phosphorus-depleted biochar design - Qin, Hongyi; Huan, Xinyu; Cui, Jingyi; Zhou, Yujun; Wang, Shijie; Liu, Shubin; Xing, Yuhui; Yu, Xiaoqian (Frontiers in Environmental Science, 2025)
PurposeBiochar application is considered a promising strategy for mitigating agricultural phosphorus (P) shortages. However, it remains uncertain whether biochar enhances soil phosphorus availability for crops beyond functioning as an external phosphorus source. Additionally, the role of phosphorus-solubilizing bacteria (PSB) in phosphorus transformation during biochar amendment is poorly understood, including whether PSB exerts a net positive or negative effect.MethodsFour different soils were incubated with or without phosphorus-depleted biochar (PDB), followed by Hedley phosphorus fractionation and leaching column experiments. Illumina MiSeq high-throughput sequencing targeting the phoD gene was used to analyze PSB diversity and community structure. Soil phosphatase activity and related properties were quantified.ResultsHedley fractionation revealed that PDB application reduced labile phosphorus while increasing HCl-extractable and residual phosphorus across all soils. Leaching experiments confirmed that PDB reduced inorganic and total phosphorus leaching in all soil types. Acid phosphatase activity was inhibited by PDB in upland soils (a peach orchard, a tea plantation, and a vegetable field). phoD-based sequencing indicated an increased relative abundance of dominant PSB genera in upland soils but a decreased abundance in paddy soils under PDB treatment. PDB did not significantly alter PSB diversity.ConclusionPhosphorus-depleted biochar reduces potentially available phosphorus fractions and mitigates phosphorus leaching, supporting aquatic ecosystem protection. However, it does not enhance short-term soil phosphorus fertility in agricultural systems. Both the mechanisms underlying PSB abundance shifts after biochar application and the ways in which plants respond to the altered P fractions require further investigation.